Pengembangan Evaluasi Pembelajaran Tematik Dengan Menggunakan Rubrik Kelas IV di Gugus IV Kecamatan Samarinda Ulu - Nurhayati; Hardoko; Warman (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2019)
This study aims to (1) find out the facts of learning in the field towards evaluating thematic learning using the grade IV elementary school rubric; (2) knowing the feasibility of evaluating thematic learning by using the rubric in grade IV elementary school students; (3) knowing the effectiveness of evaluating thematic learning by using the rubric in grade IV elementary school students. This research is a Research and Development (R & D) study with a procedural model that adapts research procedures according to Borg and Gall which can be done in 10 stages (1) research and information collecting, (2) planning, (3) developing preliminary from products, (4) preliminary field testing, (5) main product revision, (6) playing field testing and (7) operational product revision, (8) operational field testing, (9) final product revision, (10) Dissemination and distribution. Evaluation development used is the rubric feasibility assessment sheet using a Likert scale which is made in the form of a checklist and teacher response questionnaire as well as a questionnaire for expert validation. The technical data analysis used in this study is qualitative and quantitative data. The results of this study are as follows. First, the fact of learning in the field towards the development of learning evaluations by using Rubrics after going through the introduction and experiment stages of evaluating students by using rubrics, the teacher who initially did not understand the rubric now understood the rubric. can be seen from the difference in the average pre-test and post-test, namely 52.2 and 88.06. Second, the feasibility of Evaluation of Thematic Learning by using Rubric with 2 material expert Validator Tests of 94.28% and 2 education expert Validator tests of 95%. Third, the effectiveness of evaluating thematic learning by using Rubrics in small group trials was 86.67%, and large group tests were 85.04%.